O zmianie instytucjonalnej w Europie w okresie kryzysu - GROSSE, TOMASZ GRZEGORZ (Rocznik Integracji Europejskiej, 2013)
The purpose of this paper is to analyze the specificity of institutional changes taking place in the framework of European integration, with particular emphasis on the crisis. Have these changes been increasingly often introduced by non-democratic methods in order to improve their efficiency? Regardless of whether they are gradual (incremental) or radical, are they implemented as a result of informal and discreet agreements reached in the restricted circles of the political and official elite, and bypassing citizens? Can one refer to national democracy without harming the progressing integration of the Old Continent? The analysis is based on two examples – the amendments to EU treaties concluded by the establishment of the Lisbon Treaty in 2007 and expanding the powers of the European Central Bank at the time of the eurozone crisis.